Temporal and biting dynamics of the chromosomal inversion 2La in the malaria vectors Anopheles gambiae and Anopheles coluzzii in Bangui, Central African Republic - Sangbakembi-Ngounou, Claire; Ngoagouni, Carine; Akone-Ella, Ousman; Kengne, Pierre; Costantini, Carlo; Nakouné, Emmanuel; Ayala, Diego (Frontiers in Ecology and Evolution, 2022)
The chromosomal rearrangement 2La has been directly involved in the ecological and deadly epidemiological success of the malaria mosquitoes Anopheles gambiae and Anopheles coluzzii in sub-Saharan Africa. However, little is known about the biological and ecological factors that drive the local and temporal dynamics of this inversion in both species. Here, we performed a year-round longitudinal survey in Bangui, Central African Republic. We monthly sampled An. gambiae and An. coluzzii mosquitoes indoor and outdoor using human landing catches for 48 hours non-stop. We molecularly karyotyped all specimens to study the 2La inversion frequency variations, and monitored the mosquito spatial and temporal biting behavior throughout the year. In total, we successfully karyotyped 5121 An. gambiae and 986 An. coluzzii specimens. The 2La inversion frequency was higher in An. coluzzii than in An. gambiae across the year. In An. gambiae and An. coluzzii, the inversion frequency or karyotypes did not influence the biting behavior, either location or time. Moreover, the inversion frequency variation in both species was also independent of local climatic changes. Overall, our results revealed that in Bangui, the 2La inversion segregates at different frequency in each species, but this is not influenced by their trophic behavior. Studying the impact of urban settings and the population genetic structure of these two An. gambiae complex members could bring insights into the intrinsic relationship between 2La inversion and local conditions. More studies are needed to understand the polymorphic equilibrium of this inversion in Bangui.